Towards probing for hypercomplex quantum mechanics in a waveguide interferometer. (29th September 2021) - Gstir, S; Chan, E; Eichelkraut, T; Szameit, A; Keil, R; Weihs, G
Abstract: We experimentally investigate the suitability of a multi-path waveguide interferometer with mechanical shutters for performing a test for hypercomplex quantum mechanics. Probing the interferometer with coherent light, we systematically analyse the influence of experimental imperfections that could lead to a false-positive test result. In particular, we analyse the effects of detector nonlinearity, input-power and phase fluctuations on different timescales, closed-state transmissivity of shutters and crosstalk between different interferometer paths. In our experiment, a seemingly small shutter transmissivity in the order of about 2 × 10 −4 is the main source of systematic error, which suggests that this is a key imperfection to monitor and mitigate in future experiments.